Electrochemical studies of carbon-based materials - Wisetsuwannaphum, S (2014)
Graphene, as a recently discovered carbon allotrope, possesses with it many outstanding properties ranging from high electrical conductivity to great mechanical strength. Single layer graphene can be prepared by mechanical cleavage of graphite or by a more sophisticated method, CVD. However, the scale-up process for these preparation techniques is still unconvincing. Solution-processed graphene from exfoliation of graphite oxide on the other hand provides an alternative prospect resulting in the formation of graphene nanoplatelets (GNPs), which can be readily manipulated to tailor-suit various application demands. The main aim of the thesis is to explore the possibility and availability of this versatile method to produce graphene nanoplatelet and its composites with good all-round performance in energy and bioanalytical applications. A range of physical and chemical characterisation techniques were utilised including SEM, TEM, AFM, XPS, XRD, DLS, FTIR, Raman and UV-Vis spectroscopy in order to investigate the structural and chemical information of the graphene-based materials prepared. Functionalisation of graphene oxide with polyelectrolyte polymer could facilitate deposition of platinum nanoparticles in the formation of Pt-GNPs composites. The resultant composite was employed for bioanalytical application in the detection of an important neurotransmitter, glutamate, based on glutamate oxidase enzyme. The performance of Pt-GNPs based glutamate sensor exhibited enhanced sensitivity and prolonged stability compared to the sensors based on Pt decorated diamond or glassy carbon electrodes. The significant interfering effect from concomitant electrochemically active biological compounds associated with Pt-GNPs electrode however could be alleviated via opting for Prussian blue deposited GNPs electrode instead. The oppositely charged Pt-GNPs due to different functionalising polymers were also subject to self-assembly, which was enabled by the electrostatic interaction of the opposite charges of Pt-GNPs. The self-assembled film showed enhanced mechanical stability than the conventional drop-casted film and provided reasonably good activity towards oxidation of hydrogen peroxide. Three-component composite of graphene, nanodiamond and polyaniline was prepared via in-situ polymerisation for usage as an electrode material in electrochemical capacitors ("supercapacitors"). The addition of graphene was shown to significantly enhance specific capacitance while nanodiamond could improve the stability of the electrode by strengthening the polymer core. Another approach to produce a supercapacitor was via electrodeposition of nickel and cobalt hydroxides on graphene oxide film corporated with bicarbonate salt. The film was then subject to thermal reduction of GO and expansion of graphene layers within the film was observed. This leavening process enhanced the surface area of graphene film and thus the higher specific capacitance was obtained. The decoration of nickel and cobalt hydroxides onto the film also boosted the specific capacitance further however the poor cycling stability of the heated film still remained an issue. Graphene nanoplatelets were also used as a support for electrodeposition of Pt nanoparticles for methanol oxidation in acidic media. The preferential phase of the Pt deposited and large surface area of graphene in comparison to other carbon supports studied led to good catalytic activity being observed.